Inovasi Pengolahan Limbah Pasar Terfermentasi untuk Pelet Ikan pada Pembenihan Ikan Air Tawar di Wilayah Perdesaan - Arifin, M.; Ningsih, Radna; Sipahutar, Erwinsyah; Oktrison; Elfina, Sri (Lembaga Riset Cendekia, Yayasan Berkah Putera Indonesia, 2024)
Traditional market waste, such as vegetables, fruit and other organic waste, often becomes a problem in environmental management in rural areas. One potential solution is to process market waste into alternative feed ingredients for freshwater fish hatcheries. This research aims to develop innovations in processing fermented market waste into fish pellets, which can improve the quality of fish feed while reducing environmental impacts. In this research, market waste is fermented with certain microbes to turn it into fish pellets which are rich in nutrients. The research results show that the use of fermented market waste can produce effective and environmentally friendly fish pellets for freshwater fish hatcheries. The processing method used has the potential to reduce dependence on commercial fish feed and optimize available local resources